Pengaruh Kompensasi, Lingkungan Kerja Terhadap Kinerja Guru Melalui Motivasi Kerja Di SMA Kristen Kanaan - Romantika Putri Delima; Agus Fauzi (Pasca Sarjana Universitas Satya Negara Indonesia, 2019)
Based on the results of the analysis it is known that of the two structural models studied, in the first model, Work Motivation as an endogenous variable, Compensation is the dominant factor affecting Work Motivation when compared to the Work Environment. In structural model 2 which places Performance as an endogenous variable, it is known that Work Motivation is the dominant factor, then compensation and finally work environment. Based on these findings, the priority of increasing compensation and work environment can be done through increasing work motivation, in addition to the work environment and work motivation of the teacher. The indirect effect of compensation on performance through motivation has an effect of 28.6% and followed by the indirect effect of the work environment on teacher performance through work motivation by 16%.